THE EFFECT OF AUDIT ENGAGEMENT PERIOD, AUDIT ROTATION, AND FIRM SIZE ON AUDIT QUALITY WITH AUDIT COMMITTEE AS A MODERATION (EMPIRICAL STUDY IN MANUFACTURING COMPANIES LISTED ON BEI 2011-2016) - Sartika, Maya (International Journal of Public Budgeting, Accounting and Finance, 2019)
This study aims to determine and analyse the effect of the audit engagement period, audit rotation, and firm size on audit quality with the audit committee as moderating manufacturing companies listed on the Indonesia Stock Exchange. This research is associative causal research using secondary data. The population of this study is 149 companies which are manufacturing companies listed on the Indonesia Stock Exchange in 2011-2016. The sampling technique used was purposive side with the number of observations 168 (28 companies x 6 years). The analytical method used is logistic regression analysis and MRA (Moderated Regression Analysis) using SPSS software (Statistical Package for the Social Science). The results of this study prove that the audit engagement period has a significant effect on audit quality, while audit rotation and firm size have no significant effect on audit quality. The audit committee significantly moderates the audit engagement period with audit quality. The audit committee does not significantly moderate audit rotation on audit quality. The audit committee also does not significantly moderate the firm size on audit quality.